Pengaruh Workload dan Work Incivility terhadap Turnover Intention melalui Burnout pada Pekerja Gen Z Di Kota Malang - Alisca Umi Lestari; Fauzan Almanshur (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
Human resources are a vital asset for organizations. Therefore, companies need individuals who can adapt to the dynamic work environment, especially due to technological advancements. This study aims to examine the influence of workload and workplace incivility on turnover intention through burnout among Generation Z workers in Malang City. A quantitative approach was used, with the population consisting of all Gen Z workers in Malang. A total of 97 respondents were selected using the Lemeshow formula. The data were analyzed using the Partial Least Square (PLS) technique. The results show that both workload and workplace incivility significantly affect turnover intention and burnout. Furthermore, burnout mediates the relationship between workload and turnover intention, as well as between workplace incivility and turnover intention. These findings provide valuable insights for companies in managing factors that influence turnover intention.